Adsorption of Cu (II) from Aqueous Solutions by Sumac (Rhus coriaria L.) Tannins - Ugur, Ahmet Luetfi; Ozgur, Mahmure Ustuen; Gumrukcu, Guelsah (SPRINGER, 2009)
In this study, a new natural adsorbent (sumac leaves) for removing Cu (II) ion from the aqueous solutions has been investigated. Leaves of sumac were obtained from Siirt, Turkey. The tannins were extracted with acetone:water (70:30, v/v) mixture from the leaves of sumac. For the total tannin determination Folin-Ciocalteu method was used and tannin content was found 27%. In batch experiments, pH profile, adsorption time, adsorbent/liquid ratio, initial concentration of metal ions, adsorbent amount, particle size of adsorbent and temperature were performed to determine binding properties of adsorbent for the Cu(II) ions. The concentrations of the metal ions in solutions before and after adsorption were measured with an atomic absorption spectrophotometer.
Keywords: Cu(II) adsorption; Rhus coriaria L.; sumac leaves; tannins; HEAVY-METALS; SORPTION; REMOVAL; Biochemistry & Molecular Biology; Chemistry